Characteristics of Japanese patients with eosinophilic fasciitis: A brief multicenter study. Issue 12 (29th August 2020) - Yamamoto, Toshiyuki; Ito, Takashi; Asano, Yoshihide; Sato, Shinichi; Motegi, Sei‐ichiro; Ishikawa, Osamu; Matsushita, Takashi; Takehara, Kazuhiko; Makino, Takamitsu; Okiyama, Naoko; Fujimoto, Manabu; Jinnin, Masatoshi; et al.
Abstract: Eosinophilic fasciitis is a relatively rare cutaneous fibrotic condition affecting the deep fascia of the extremities, with or without peripheral blood eosinophilia. To examine the characteristics of Japanese patients with eosinophilic fasciitis, we conducted a brief, multicenter, retrospective survey at seven university hospitals. In total, 31 patients were identified as having eosinophilic fasciitis, among whom 30 patients fulfilled the Japanese diagnostic criteria. The male : female ratio was 2.3:1, and the mean age was 47.7 years. Three of the patients were under 20 years old. The possible triggering factors included muscle training, sports, walking or sitting for a long time, physical work, insect bite and drug. Co‐occurrence of morphea was observed in nine cases (29%), and malignancies were associated in three (two hematological malignancies and one internal malignancy). Immunological abnormalities in the serum showed positive antinuclear antibody, positive rheumatoid factor, increased aldolase levels and increased immunoglobulin G levels. The patients were treated with either monotherapy or combination therapy by oral prednisolone (20–80 mg/day), methotrexate (6–10 mg/week), cyclosporin (100–150 mg/day), mizoribine, infliximab and phototherapy. Methylprednisolone pulse therapy was performed in six cases. By contrast, spontaneous improvement due to resting only was observed in two cases, and skin hardening was improved by withdrawal of the anticancer drug in one case. This study suggests several characteristics of Japanese patients with eosinophilic fasciitis, namely male predominance, rare pediatric occurrence, immunological abnormalities and coexistence with morphea. Systemic prednisolone is the first‐line therapy, but pulse therapy is occasionally required for severe cases. The triggering events of physical stress are not so frequent as have previously been reported, and various factors or even unknown factors may be associated with the induction of eosinophilic fasciitis.